Sunburn [compact disc, unabridged] : a novel - Lippman, Laura, 1959- (Harper Audio, 2018)
They meet at a local tavern in the small town of Belleville, Delaware. Polly is set on heading west. Adam says he's also passing through. Yet she stays, and he stays - drawn to this mysterious redhead whose quiet stillness both unnerves and excites him. Over the course of a punishing summer, Polly and Adam abandon themselves to a steamy, inexorable affair. Still, each holds something back from the other - dangerous, even lethal secrets. Then someone dies. Was it an accident or part of a plan? By now Adam and Polly are so ensnared in each other's lives and lies that neither one knows how to get away - or even if they want to. Is their love strong enough to withstand the truth, or will it ultimately destroy them? Something - or someone - has to give. Which one will it be?